PENGARUH STRATEGI GREEN MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK MOLTO ULTRA SEKALI BILAS DI PADANG - Puspita Wulan Dhari; Alhapen Ruslin Chandra; Afifah Afifah (Politeknik Negeri Padang, 2018)
Green marketing is a marketing strategy that contains environmentally friendly element. One product that has implemented a green marketing strategy is Molto Ultra Sekali Bilas. The marketer plays a role in environmental preservation processes which is saving water resources. This study aims to determine the effect of the green marketing mix strategy on Molto Ultra Sekali Bilas to consumer purchasing decisions in Padang. Data collection is done by distributing questionnaires. Using multiple linear regression method, known that of the four green marketing variables consisting of green product, green price, green promotion and green place, only green product has significant effect on Molto Ultra sekali bilas consumer purchasing decisions partially. However, all variables of green marketing have a significant effect simultaneously on Molto Ultra's consumer purchasing decisions.